Prototype of Gas Leak Detector System Using Microcontroller and SMS Gateway - Marchel Thimoty Tombeng (Fakultas Ilmu Komputer, Universitas Klabat, 2017)
On of the very important things in human life is home safety. Home Safety refers to the awareness of risks and potential dangers in and around home which may cause bodily harm, or even death. Awareness and vigilance is indispensable in preventing the threatening risks and potential dangers. Therefore, people needs a timely warning information about gas leak for prevention of home safety threatening risks and potential dangers. This warning information will allow people, users, or residents to reduce the risks and potential dangers caused by gas leak, especially when they are away from home. This paper describes the development of system technology regarding the gas leak detector which integrates the MQ2 gas sensor, Arduino Uno R3 Microcontroller and the Sim900 SMS Gateway. Keywords : MQ2 Sensor, Arduino Uno R3, Sim900, LPG